Thomas Schmidt-Beste (ed.), The Motet Around 1500: On the Relationship of Imitation and Text Treatment? (2012); and Albert Clement and Eric Jas (eds), Josquin and the Sublime (2011) - Collins, Denis (Journal of the Society for Musicology in Ireland, 2015)
A review of Thomas Schmidt-Beste (ed.), The Motet Around 1500: On the Relationship of Imitation and Text Treatment? Centre d’études supérieures de la Renaissance. Collection ‘Épitome musical’ (Turnhout, Belgium: Brepols, 2012), ISBN 978-2-503-52566-2; and Albert Clement and Eric Jas (eds), Josquin and the Sublime. Proceedings of the International Josquin Symposium at Roosevelt Academy. Middleburg 12–15 July 2009. Centre d’études supérieures de la Renaissance. Collection ‘Épitome musical’ (Turnhout, Belgium: Brepols, 2011), ISBN 978-2-503-54271-3.